Upconversion thermal enhancement of 2H11/2→4I15/2 of Er3+ and blue emission of impurity Tm3+ in Sr3(PO4)2:Er3+/Yb3+. Issue 6 (27th July 2022) - Cui, Hongqiang; Cao, Yongze; Li, Ying; Li, Lei; Zhang, Yuhang; Li, Guojian; Wang, Yichao; Li, Xiangping; Chen, Baojiu
Abstract: A series of Sr2.99‐x (PO4 )2 :.01Er 3+ /xYb 3+ ( x  = .02, .04, .06, .08, .10) phosphors in the presence of impurity Tm 3+ were synthesized by high temperature solid‐state method, and X‐ray diffraction results show that these samples are pure R‐3 m(166) space group phase. The upconversion luminescence (UCL) of Er 3+ and impurity Tm 3+ under 980‐nm laser excitation were investigated, and the results show that the intense blue UCL of impurity Tm 3+ and thermal enhancement of 2 H11/2 → 4 I15/2 of Er 3+ simultaneously exist. When Er 3+ doping concentration is kept at .01, both the blue UCL intensity of impurity Tm 3+ and green and red UCL intensity of Er 3+ reach the maximum at Yb 3+ doping concentration of .08. The thermal enhancement effect of 2 H11/2 → 4 I15/2 of Er 3+ was observed as high as 3.27 times from 303 to 723 K, which is because of lattice distortion and phonon‐assisted transition. In addition, the optical temperature performance of Sr2.91 (PO4 )2 :.01Er 3+ /.08Yb 3+ sample was studied, and the maximum absolute temperature sensitivity was calculated as .00623 K −1 at 538 K. This study suggests that Sr3 (PO4 )2 :Er 3+ /Yb 3+ phosphors in the presence of impurity Tm 3+ have a promising application prospect as optical temperature sensor at high temperature.